The API Performance Contract. - SPROULL, ROBERT F.; WALDO, JIM (Communications of the ACM, 2014)
The article examines application programming interfaces (API) in computer programming. The performance contract, the expectations of API performance from users of a computer system and its software, is considered. A taxonomy of API functions is offered. API behavior in response to call failures is discussed. The dependence of major application programs on adherence to a performance contract is discussed. Means by which programmers can prevent violations of API performance contracts are examined including selection of program structure, maintaining contract stability and explicitly including the contract in API specifications.